Analisis Determinan Kemiskinan di Kabupaten Kulonprogo Tahun 2018-2022 - Christi, Oktaria Denanda; Hadiwijoyo, Suryo Sakti; Purnomo, Daru (Innovative: Journal Of Social Science Research, 2024)
This study aims to analyze the determinant factors that influence the poverty rate in Kulonprogo Regency during the 2018-2022 period. This research uses quantitative approach with the multiple linear regression method to identify the main determinants of poverty in the area. The data used used in this study is panel data sourced from BPS Kulon Progo Regency, which is also used as a variable in this study. Kulon Progo Regency which is also used as a variable in this study which includes the poverty rate, economic growth, unemployment rate, and poverty rate. variables in this study which include poverty rate, economic growth, unemployment rate, and population, and population. The results showed that partially Partially, economic growth has a positive and significant effect on the poverty rate in Kulon Progo Regency. Meanwhile, the unemployment rate has a positive and significant effect to the poverty rate of Kulon Progo Regency. Meanwhile, the total population has a positive and significant effect on the poverty rate of Kulon Progo Regency